A vulval leiomyoma: a rare camouflaging tumor - Mehta, Samir; Jain, Samrudhi; Borole, Supriya; Gupta, Salonee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Uterine leiomyomas are a benign tumor of human uterus and common problem in gynecology. Despite this, leiomyomas of the vulva are rare, masquerading, and usually misdiagnosed as Bartholin cyst preoperatively. These benign smooth muscle tumors are typically painless, solitary, and well circumscribed and can affect female of any age group. We hereby present a case of a 39-year-old female that presented in OPD at ESIC model hospital, Bapunagar, Ahmedabad with left labial mass and was misdiagnosed as Bartholin cyst initially and later on histopathology final diagnosis of vulvar leiomyoma was made.